Effect of pedicle screw diameter on screw fixation efficacy in human osteoporotic thoracic vertebrae. (21st March 2018) - Lai, Dar-Ming; Shih, Yu-Tang; Chen, Yi-Hsing; Chien, Andy; Wang, Jaw-Lin
Abstract: The selection of an ideal screw size plays a crucial role in the success of spinal instrumentation as larger diameter screws are thought to provide better fixation strength but increase the risk of pedicle failure during insertion. On the other hand, smaller diameter screws are with lesser risk of pedicle breakage but are thought to compromise the stability of the instrumentation. By investigating the relationship between screw diameter and the pullout strength of pedicle screws after fatigue loading, this study seeks to find quantitative biomechanical data for surgeons in determining the most ideal diameter size screws when performing surgical implementations on osteoporotic vertebrae. Twenty-seven osteoporotic (BMD ranged: 0.353–0.848 g/cm 2 ) thoracic vertebrae (T3-T8) were harvested from 5 human cadavers. Two sizes of poly-axial screws (5.0 mm × 35 and 4.35 mm × 35) were implanted into each pedicles of the vertebrae by an experienced surgeon. Specimens were randomly distributed into control group, fatigue group of 5000 and 10, 000 cycles with peak-to-peak loadings of 10–100 N at 1 Hz. Each specimen was then axial pullout tested at a constant rate of 5 mm/min. The ultimate pullout strength (N) & stiffness (N/mm) were obtained for analysis. The results showed that although the larger diameter screws achieved superior pullout strength immediately after the implantation, both sizes of screws exhibited comparable pullout strengths post fatigue loading. This indicates that the smaller diameter screws may be considered for surgical techniques performed on osteoporotic vertebrae for reduced risk of pedicle breakage without sacrificing fixation strength.